A cultura de segurança do paciente em um hospital de ensino de Minas Gerais - LUIZ, Raíssa Bianca (2013)
The issue of patient safety has become a focus of attention for health care organizations that encourage the adoption of a culture of safety in order to reduce adverse events and improve the quality of care provided. This research aimed to assess the culture of patient safety from the perspective of the professional health care team in a teaching hospital of Triangulo Mineiro. This is an observational, cross-sectional quantitative approach, performed with 556 professionals. This study was approved by the Ethics in Research UFTM in opinion n°. 2306. Data were collected with health professionals linked to UFTM and Foundation of Research and Uberaba, using the Safety Attitudes Questionnaire (SAQ), translated and validated for the Portuguese language, Brazil. This instrument consisted of sociodemographic and professional plus six areas related to safety culture. Data analysis used the Statistical Package for Social Sciences (SPSS). Qualitative variables were analyzed using descriptive statistics and quantitative measurements were descriptive of centrality and dispersion. To check the culture of patient safety from the perspective of health professionals, we calculated the final score of the instrument by the average of all the items of the instrument multiplied least one and twenty-five. For bivariate analysis of the influence of categorical variables on the SAQ scores was used for dichotomous categorical variables, the Student t test for variables with three or more categories and the analysis of variance for ordinal variables, the Spearman correlation (α = 0,05). To identify predictors of scores on the SAQ was used multiple linear regression having as main outcome domain security climate (α =0,01). It was found that most professionals studied were female (76,6%), providing assistance to adult patients (54,0%), had only welfare offices, crowded in the critical area (51,5%), not being graduate (57,6%), with no other employment relationships (70,9%) and linked to UFTM (53,8%). A greater proportion of professionals with five to ten years in the specialty (24,1%) and 11-20 years of time in the institution (29,0%) and training time (31,8%). The overall score of the instrument was 61,8 (SD= 13,7) and median 63,3, the domain score was the best job satisfaction 80,5 (SD= 17,7) and median 85,0 and domains with lower scores were the perception of the management of the unit and the hospital (mean 54,4, SD= 19.5, median 52,3) and working conditions (mean 53,5, SD = 26,3, median 50,0). The business sector with the best overall score was the transfusion service (78,3, SD = 7,7) and the worst service standardization of materials (32,4). Among the professionals, the category audiologist showed the best overall score (71,5) and the category Occupational Therapist worst score (28,8). Variables that showed significant associations in bivariate analysis were professional performance, time of work in the specialty, training time, time in the institution, the professional category and institutional affiliation. In multiple linear regression analysis, was found as a predictor variable professional activities (professional assistance and non- assistance) for the domain of perception management unit and hospital, and the professionals had better perception for domain entity in relation to care (p=0,01). The identification of areas that need improvement within the institution and among professionals as well as for assessment of organizational safety culture, guiding the development of strategies to ensure patient safety in healthcare organizations.